Identification of Enterobacter sakazakii in raw milk for dry infant formula production - Бергилевич, Александра Николаевна; Гришина, Евгения Анатольевна; Касянчук, Виктория Викторовна (Eastern-European Journal of Enterprise Technologies, 2014)
Microorganism E. sakazakii was first identified inUkrainein general and in raw cow’s milk in particular. Cultural, morphological and biochemical properties of 8 strains of this microorganism were studied, whereby one of the strains has been deposited with the National Collection. E. sakazakii was identified in raw milk in 22.3 % of cases. Direct correlation between the total bacterial milk pollution and E. sakazakii identification was determined. Average E. sakazakii count in 1 ml of raw milk, in which the total microbial count was up to 100.000 CFU/ml, was from 3 CFU/ml to 10 CFU/ml. In milk with high total bacterial pollution level − 500.000 CFU/ml, the E. sakazakii count was on average 150 CFU/ml − 200 CFU/ml. Optimal raw milk storage conditions:4 °Cfor 12−24 hours, in which the E. sakazakii growth and development slows down were determined. Thermoresistivity level of E. sakazakii, which is58 °C−60 °Cwas defined. It was proved that the raw cow’s milk can be a potential source of contamination of dry infant formulas by Enterobactersakazakii in case of failure of proper control over its obtaining, storage, transportation and processing and therefore pose a threat to children under the age of 12 months, who are fed by these formulas. It is recommended to pasteurize raw milk for producing dry infant formulas at a temperature no less than70 °C.